A secular need : Islamic law and state governance in contemporary India - Redding, Jeff (Seattle : University of Washington Press, 2020)
"Islamic law's relationship to secular governance is a fraught one in contemporary discussions. Whether from the perspective of Islamic law's advocates, secularism's partisans, or publics caught in the crossfire, many people see the relationship between Islam and secularism as antagonistic. Moreover, the relationship between Islamic law and secularism seems increasingly discordant, with recent developments in the United States (e.g., calls for "shari'a bans" in U.S. courts), Western Europe (such as legal limitations on headscarves and mosques), and the Arab Middle East (such as conflicts between secularist old-guards and Islamist revolutionaries) indicating that unsteady coexistences are transforming into outright hostilities. This book's exploration of an Indian non-state system of Muslim dispute resolution-formally known as the dar ul qaza system, but commonly referred to as a system of "Muslim courts" or "shariat courts"-challenges conventional narratives about the inevitable opposition between Islamic law and secular forms of governance, and the impossibility of their coexistence. Moreover, it demonstrates how secular law and governance in India does not and cannot work without the significant assistance of non-state Islamic legal actors. For example, the conciliation-oriented Indian family court system is insufficient for handling divorce petitions brought by Muslim women seeking to unilaterally disassociate from their Muslim husbands. This volume shows how in these situations and others, Indian state secularism needs the Islamic non-state-so much so that this intense need often erupts into a complicated set of love-hate politics towards India's Muslims"--
Introduction : Indian Secularism and Its Relationship to Islamic Law -- Muslim and Mundane : Historical and Contemporary Aspects of Dar ul Qazas -- Secularism and "Shari'a Courts" : A Constitutional Controversy -- Secular Emotion and the Rule of Law : The Case of Ayesha -- Secular Need and Divorce : India and the Geopolity -- Illegitimacy and Indigeneity : Secular Courts and Muslim Dar ul Qazas -- Conclusion : Feeling Like a State
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 03, 2020).
JSTOR
Keywords: Law -- India -- Islamic influences; Islamic law -- India; Legal polycentricity -- India; Muslims -- Legal status, laws, etc. -- India; Domestic relations -- India; Islamic courts -- India; Droit -- Inde -- Influence islamique; Droit islamique -- Inde; Pluralisme juridique -- Inde; Tribunaux islamiques -- Inde; HISTORY / Asia / India & South Asia; Domestic relations; Islamic courts; Islamic law; Law -- Islamic influences; Legal polycentricity; Muslims -- Legal status, laws, etc; India